Post-traumatic hydrocephalus after decompressive craniectomy. (November 2021) - Missori, Paolo; Currà, Antonio; Peschillo, Simone; Paolini, Sergio
Highlights: Hydrocephalus after severe traumatic brain and decompressive craniectomy is not well determined. The authors analyze the medial margin distance from midline after decompressive craniectomy. The study drives to consider nonsignificant the medial craniectomy margin distance from midline.